Providing Graft Tension in ACL Reconstruction with Preservation of the Hamstring Tibial Attachment Site: A Report on the Technique and Clinical Results - Sever, Gökhan Bülent; Cankuş, Cenk (European Journal of Therapeutics, 2023)
Objective: Hamstring autograft is the most commonly used graft in the surgical technique for anterior cruciate ligament reconstruction. Different femoral fixation materials can be used in this surgery. This study aimed to share the surgical technique for anatomic single-band anterior cruciate ligament reconstruction, preserving hamstring tibial attachment site and the clinical results. Methods: Total 42 consecutive patients who were operated for anterior cruciate ligament rupture were included in the study. Anatomic single-band anterior cruciate ligament reconstruction was performed for patients without disjointing the hamstring distal attachment site. Patients were evaluated in terms of age, sex, four-arm tendon length, total tunnel length from the hamstring attachment site, femoral tunnel length, length of the graft in the femoral tunnel, and the average tendon length calculated as per the tunnel length. The mean follow-up duration was 17 months. The patients were evaluated clinically using the Tegner activity score, Lysholm score, and International Knee Documentation Scale (IKDC). The anterior translation of the tibia was evaluated with a KT 1000 device. Results: The preoperative and postoperative mean Tegner, IKDC, and Lysholm scores were improved significantly. Conclusion: The surgical method for anatomic single-band anterior cruciate ligament reconstruction with preservation of the hamstring attachment site is a useful technique. Moreover, this technique is cost-effective and did not increase patient morbidity.